Facile hydrothermal synthesis of polyimide/Fe3O4 aerogel microspheres as magnetically controllable oil sorbents. (1st February 2023) - Jin, Xu; Zhang, Li; Tao, Jiaping; Bai, Jie; Yang, Changqing; Zhang, Chenjun; Meng, Siwei; Wu, Juntao
Highlights: Novel polyimide/Fe3 O4 aerogel microspheres are prepared via solvothermal method. PFAM exhibits superhydrophobicity and superoleophilicity in air. The embedded Fe3 O4 nanoparticles make the PFAM rough and magnetically controllable. PFAM has excellent adsorption capacity and can be promising sorbents in tight space. Abstract: Novel polyimide (PI) /Fe3 O4 aerogel microspheres (PFAM) are designed and prepared via solvothermal method. The resultant PFAM exhibit superhydrophobicity and superoleophilicity in air; as well as superoleophilicity in water. The contact angle of PFAM surface to water is 148.4 ± 2.4° (in air) and to oil is closed to 0° (in air and in water). The embedded Fe3 O4 nanoparticles impart the PFAM roughness in the nano- and microscale, thus effectively enhancing the wettability of PI matrix. Moreover, due to the remote magnetic controllability, micro size, as well as the high thermal stability, outstanding resistance to solvent and superior mechanical properties of PI, the PFAM can be used to extract oil in narrow space under severe ambient conditions. The oil/solvent absorption capacities of PFAM are in the range of 82–147 g/g, making them promising sorbents in extracting unconventional oil underground.